Comparative study on the quality and drying kinetics of temulawak by open-sun drying and biomass pyrolysis-integrated flat-bed dryer - Rosdanelli Hasibuan; Juliza Hidayati; Muhammad Khuwailid; Thiodorus Marvin Tjandra; Viqry Pramananda (Center of Biomass & Renewable Energy (CBIORE), 2026)
Temulawak is a medicinal plant which is known for its active compound, curcumin. To extend its shelf life, freshly harvested rhizomes are typically subjected to drying to reduce their moisture content. However, the drying process must be carefully controlled to prevent curcumin degradation which is thermolabile. Despite its continued popularity for agricultural commodities drying because it requires minimal equipment and no operational expenses, open-sun drying (OSD) leaves the product vulnerable to external hazards such as dust, environmental pollutants, and ultraviolet exposure. A more suitable alternative is the flat-bed dryer (FBD) system. This study presents a comparison between OSD and an FBD integrated with a pyrolysis reactor for the drying of temulawak. The results demonstrated that the FBD significantly shortened the drying duration to 705 min at 70°C and 1.0 cm-thickness, compared with 2,490 min for OSD at the same thickness. The drying rate in the FBD reached 49.40–56.00 g/m2.min, substantially higher than OSD (14.60–16.00 g/m2.min). Curcumin content increased in both drying methods as a consequence of moisture reduction, with the FBD achieving 14.82 ppm within a markedly shorter drying time than OSD. Morphological analysis revealed cell-wall shrinkage and deformation of starch granules after drying, particularly in FBD-dried temulawak. Elemental composition analysis showed a considerable increase in mineral fractions after drying, corresponding to the reduction in moisture content. Drying kinetic modelling indicated that the Hasibuan–Daud model provided the best fit for FBD data, whereas the Midilli model offered the closest agreement with the experimental data obtained from OSD. The effective moisture diffusivity obtained for the FBD was 4.970 × 10-8 m2/s, significantly higher than that of OSD, with an activation energy of 29.53 kJ/mol. Overall, the use of an FBD integrated with a pyrolysis reactor offers a sustainable and efficient alternative for the high-quality drying of medicinal plants, outperforming conventional OSD.